Review of Tarsonemus heterosetiger Mahunka, 1974 (Acari: Heterostigmatina: Tarsonemidae)—an unusual species from Central Africa warranting supraspecific recognition - Magowski, Wojciech Ł. (Zootaxa, 2020)
Tarsonemus heterosetiger Mahunka, 1974 is redescribed and illustrated. The type and non-type material are annotated; its morphology is discussed. The collection data of the type series is also corrected. In order to accommodate its systematic distinctiveness, a new supraspecific taxon is proposed.